P321 Cessation of Anti-Tumour Necrosis Factor Therapy in Patients with Perianal Fistulizing Crohn's Disease: Individual Patient Data Meta-Analysis of 323 patients from 12 studies. (27th May 2021) - Ten Bokkel Huinink, S; van der Woude, J; Casanova, M J; Bouguen, G; Mak, J W Y; Molnar, T; Seidelin, J; Aurelien, A; D'Haens, G; Riviere, P; Guidi, L; Renata, B; et al.
Abstract: Background: The risk of relapse after anti-tumour necrosis factor [TNF] therapy cessation in Crohn's disease [CD] patients with perianal fistulas is unclear. We aimed to assess the risk of relapse after anti-TNF cessation in a large cohort and to identify risk factors. Methods: A systemic literature search was conducted to identify cohort studies reporting on the incidence of relapse after cessation of anti-TNF therapy in CD patients. Individual patient data [IPD] were requested from the original study cohorts. Inclusion criteria for IPD-meta-analysis (IPD-MA) included age ³ 18 years, perianal fistulizing CD as indication for start of anti-TNF therapy, minimal treatment duration ³3 doses, and remission of luminal and perianal CD at cessation of anti-TNF therapy. Primary outcome was CD relapse [either perianal or luminal]. Perianal fistula relapse was defined as recurrence of draining perianal fistula related to previous or new fistula tracks, or abscess. Luminal relapse was defined as a clinical, biochemical, endoscopic, or radiological relapse requiring treatment or dose optimization of IBD medication or surgery. In a secondary analysis, risk factors associated with relapse were assessed using multivariate logistic regression analysis. Results: A total of 307 patients from 12 studies in 9 countries were included in this IPD-MA. The median duration of anti-TNF treatment prior to therapy cessation was 14 months [IQR 6.1 – 29.9]. In 272/307 patients [89%] anti-TNF therapy was started for active perianal fistula and in 34 [11%] for both active perianal fistula and luminal CD. 169 patients [55%] developed a relapse [either perianal or luminal] after a median follow-up after cessation of 25 months [IQR 12 – 54]. Overall cumulative incidence of relapse was 31% and 43% at 1 and 2 years after anti-TNF cessation. Risk factor for CD relapse include upper GI involvement (L4) [HR 1.9], whereas older age [A3 vs A1, HR 0.48] and continuation of concomitant immunomodulators [HR 0.62] were protective factors. For a subgroup of patients with active perianal fistula and in luminal remission at start of anti-TNF, the cumulative incidence relapse rates were 25% and 43% at 1 and 2 years. No considerable differences in risk factors were found within this subgroup regarding risk of recurrence. Of the 179 patients who relapsed, 104 were retreated with anti-TNF with a response rate of 85%. Conclusion: According to this IPD-MA, approximately two-thirds of CD patients with perianal fistula remain in remission with regard to fistulizing and luminal disease during 2 years after cessation of anti-TNF therapy. Further risk stratification based on perianal fistula characteristics is required.